The importance of the degrowth concept in the 21st century - Raftowicz, Magdalena (Publishing House of Wroclaw University of Economics and Business, 2023)
The article addresses the problem of degrowth, approached as a socio-economic process reducing human pressure on the environment (the detoxification of nature) by setting alternative economic goals and recognising other boundaries (ecological and social) in the socio-economic development. Its main purpose is to systematise knowledge about degrowth and attempt to answer the question whether the concept of degrowth has a chance of becoming a new real paradigm of socio-economic development in the 21st century. A critical analysis of the source literature covering the problem of socio-economic development paradigm and the concept of degrowth was the starting point of the research. The empirical study relating to the problem of shortening food supply chains in Poland serves as an example illustrating the practical implication of degrowth. The conducted analysis showed that the concept of degrowth may become a new paradigm of socio-economic development in the 21st century. It requires, however, further changes in the institutional system as a controlled process of changes.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 113-129
Keywords: socio-economic development paradigm; degrowth; anti-goods; short food supply chains